Evaluation of spinal and epidural anaesthesia for day care surgery in lower limb and inguinoscrotal region - Asha Gupta; Sarabjit Kaur; Ranjana Khetarpal; Haramritpal Kaur (Wolters Kluwer Medknow Publications, 2011)
Background: Day care surgery is still in its infancy in India. Both regional and general anaesthesia can be used for this. Central neuraxial blocks are simple cheap and easy to perform. This study was done to evaluate usefulness of spinal and epidural anaesthesia for day care surgery. Patients & Method:100 patients were randomized to either spinal (n=50) or epidural (n=50) group anaesthetized with either 0.5% hyperbaric 2ml bupivacaine or 0.5% 20ml bupivacaine respectively. In spinal group 27 gauze quincke needle and in epidural group 18 gazue tuohy needle was used. Both the groups were compared for haemodynamic stability, side effects, complications, postanaesthesia discharge score (PADS), time taken to micturate, total duration of stay in hospital and patient satisfaction score for technique. Results: We observed that spinal anaesthesia had significantly early onset of anaesthesia and better muscle relaxation (p<0.05) as compared to epidural block otherwise both groups were comparable for haemodynamic stability, side effects or complications. Although more patients in spinal group (64% vs 48%) achieved PADS earlier (in 4-8 hours) but statistically it was insignificant. Time to micturition (6.02 0.55 v/s 6.03 0.47 hours) and total duration of stay (7.49 1.36 v/s 8.03 1.33 hours) were comparable in both the groups. Conclusion:Both spinal and epidural anaesthesia can be used for day care surgery. Spinal anaesthesia with 27 gauze quincke needle and 2ml 0.5% hyperbaric bupivacaine provides added advantage of early onset and complete relaxation.